Diastereo‐ and Enantioselective Access to Stereotriads through a Flexible Coupling of Substituted Aldehydes and Alkenes. Issue 18 (27th March 2019) - Li, Jing; Preinfalk, Alexander; Maulide, Nuno
Abstract: A flexible redox‐neutral coupling of aldehydes and alkenes enables rapid access to stereotriads starting from a single stereocenter with perfect levels of enantio‐ and diastereoselectivity under mild conditions. The versatility of the method is highlighted by the installation of heteroatoms along the tether, which enables a route to structurally diverse building blocks. The formal synthesis of (+)‐neopeltolide further demonstrates the synthetic utility of this approach. Abstract : Make it three : A flexible redox‐neutral coupling of aldehydes and alkenes gives rapid access to stereotriads, starting from a single stereocenter, with perfect levels of enantio‐ and diastereoselectivity under mild conditions. The installation of heteroatoms along the tether enables the synthesis of structurally diverse building blocks. The formal synthesis of (+)‐neopeltolide further demonstrates the synthetic utility of this approach.